Cangkrukan Activities As Confirmation of Javanese Identity Through KIPAS Counseling Model - Wahyudi, Ilham Akbar; Mappiare-AT, Andi; Fuzan, Luthfi; Kamaruddin, Mariah Binti (Buletin Konseling Inovatif, 2025)
Cangkrukan is an activity that feels right to be held in order to develop a Javanese label so that it can be realized according to the steps of the KIPAS model counseling. This study aims to provide a design for the implementation of cangkrukan activities as an affirmation of Javanese identity through KIPAS counseling model. This study reveals the labels of Javanese people with the method of symbolic interactionism. The subjects studied were customers of the Upa Jiwo coffee shop in the Merjosari area, Malang City. Data analysis uses three stages of data analysis from symbolic interactionism, namely description, categorization, and connection. The results show that there are several labels that characterize Javanese humans, namely trimo ing pandhum, unggah-ungguh, andhap asor, tepa selira, aja adigang adigung adiguna, and guyub rukun. These labels will be used as the theme of discussion in cangkrukan activities organized by the school counselor with the counselee.